Flexural Properties and Thermal Conductivity of Aluminium Nitride Filled Polypropylene Composite - Azlin Fazlina, Osman; Banjuraizah, Johar; Syed Nuzul Fadzli, Syed Adam; Sri Asliza, Md Amin; Firdaus, Abd Rahman; Lee, Lay Sin (Universiti Malaysia Perlis (UniMAP), 2008)
Organized by Universiti Malaysia Perlis (UniMAP), 9th - 12th June 2007 at Park Royal Hotel, Penang.